Burnout's syndrome in nurses in front of the pandemic: an integrative literature review (Research, Society and Development, 2021)
Objective: to identify in the scientific literature the predisposing factors for the development of Burnout syndrome in nursing professionals during the COVID-19 pandemic. Methodology: this is an integrative literature review carried out through the studies available in the Virtual Health Library, Latin American and Caribbean Literature in Health Sciences and in the Scientific Electronic Library Online portal. The criteria established for inclusion in this research were: complete and original studies made available for free, publication period between the last three years (2019 to 2021) in Portuguese. The following descriptors were used: “Burnout Syndrome”; "Nursing"; “COVID 19” for the election of scientific articles. Data were analyzed descriptively. Results: ten articles were identified, divided into three categories: studies focusing on workload, studies focusing on predictors of mental illness and studies focusing on the clinical status of patients. Conclusion: the most prominent signs among professionals were depression and anxiety, as they are continually dealing with the demands of patients' demands that are complex and severe. In addition, studies have shown that this syndrome can be triggered by factors associated with the work environment, such as the lack of human resources, physical structure and appreciation on the part of managers and employers.